Effects of barbell back squat stance width on sagittal and frontal hip & knee kinetics - Lahti, J.; Hegyi, A.; Vigotsky, A. D.; Ahtiainen, J. P. (Scandinavian Journal of Medicine & Science in Sports, 2019)
Different stance widths are commonly utilized when completing the barbell back squat during athletic general preparedness training. Width manipulation is thought to influence sagittal plane stimuli to the hip and knee extensors, the primary extensor musculature in the squat. However, how width manipulation affects frontal plane stimuli is less understood. Knowledge of hip and knee net joint moments (NJM) could improve exercise selection when aiming to improve sport-specific performance and prevent injuries. Fourteen adult amateur rugby athletes were recruited for this study. After a familiarization period, participants performed wide- (WIDE, 1.5x greater trochanter width) and narrow-stance (NARROW, 1x greater trochanter width) barbell back squats to femur parallel depth, using relative loads of 70 and 85% of one-repetition maximum. Sagittal and frontal plane hip and knee kinetics and kinematics were compared between widths. A Bonferroni-corrected alpha of 0.01 was employed as the threshold for statistical significance. Knee flexion angle was statistically greater in NARROW than WIDE (p < 0.0001, d = 2.56-2.86); no statistical differences were observed for hip flexion angle between conditions (p = 0.049-0.109, d = 0.33-0.38). Hip-to-knee extension NJM ratios and knee adduction NJMs were statistically greater in WIDE than NARROW (p < 0.007, d = 0.51-1.41). At femur parallel, stance width manipulation in the barbell back squat may provide substantial differences in biomechanical stimulus in both the sagittal and the frontal plane. In certain contexts, these differences may have clinically relevant longitudinal implications, from both a performance and injury prevention standpoint, which are discussed.